The Kingfisher illustrated encyclopedia of animals : from aardvark to zorille--and 2,000 other animals - Chinery, Michael (New York : Kingfisher Books, 1992)
Alphabetical entries provide information on the physical characteristics, behavior, and habitats of over 2,000 animals.
Includes index.
Rev. ed. of: Dictionary of animals. 1984.
Booklist.
School Library Journal.
Wilson's Junior High School.
5.7
Keywords: Animals -- Encyclopedias, Juvenile; Animals -- Encyclopedias; Animals -- Dictionaries